Photothermally enhanced antibacterial wound healing using albumin-loaded tanshinone IIA and IR780 nanoparticles - Haidong Chen; Yimei Li; Dexuan Chen; Yong Fang; Xuchu Gong; Kaikai Wang; Kaikai Wang; Chaoqun Ma (Frontiers in Bioengineering and Biotechnology, 2024)
Chronic and infected wounds, particularly those caused by bacterial infections, present significant challenges in medical treatment. This study aimed to develop a novel nanoparticle formulation to enhance wound healing by combining antimicrobial and photothermal therapy using albumin as a carrier for Tanshinone IIA and the near-infrared photothermal agent IR780. The nanoparticles were synthesized to exploit the antimicrobial effects of Tanshinone IIA and the photothermal properties of IR780 when exposed to near-infrared laser irradiation. Characterization of the nanoparticles was performed using Transmission Electron Microscopy (TEM) and spectroscopic analysis to confirm their successful synthesis. In vitro antibacterial activity was evaluated using cultures of methicillin-resistant Staphylococcus aureus (MRSA), and in vivo efficacy was tested in a mouse model of MRSA-infected wounds. Wound healing progression was assessed over 16 days, with statistical analysis performed using two-way ANOVA followed by Tukey’s post-hoc test. The nanoparticles demonstrated significant photothermal properties, enhancing bacterial eradication and promoting the controlled release of Tanshinone IIA. In vitro studies showed superior antibacterial activity, especially under photothermal activation, leading to a substantial reduction in bacterial viability in MRSA cultures. In vivo, nanoparticle treatment combined with near-infrared laser irradiation significantly improved wound closure rates compared to controls and treatments without photothermal activation. By the 16th day post-treatment, significant improvements in wound healing were observed, highlighting the potential of the combined photothermal and pharmacological approach. These findings suggest that albumin-loaded nanoparticles containing Tanshinone IIA and IR780, activated by near-infrared light, could offer an effective therapeutic strategy for managing chronic and infected wounds, promoting both infection control and tissue repair.